2018
DOI: 10.3390/nu10111608
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Condition and Body Composition, Nutrient Intake, Sociodemographic Characteristics, and Lifestyle Habits in Older Spanish Adults

Abstract: In this study, we assessed physical condition and its association with body composition, nutrient intake, sociodemographic characteristics, and lifestyle habits in older Spanish adults. In this cross-sectional study, we investigated 380 individuals (54% women; men aged 55–80 years and women aged 60–80 years) with no previously documented cardiovascular disease. A general questionnaire was used, and body weight, height, fat, appendicular skeletal muscle mass, and waist circumference were assessed. Physical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 50 publications
2
23
0
2
Order By: Relevance
“…On the other hand, there are significant associations between lifestyles, sociodemographic characteristics, and clinical variables, and compliance with the recommended daily intakes. As shown by the results found in international studies, our work concludes that living in rural areas (because there are fewer accessible services), being divorced, and being illiterate negatively influence compliance with the recommended intakes of certain nutrients [6,19,30,31]. With regard to lifestyles, as in numerous research studies, we observed that a greater physical activity improves health and, in our case, there is greater compliance with the recommendations of Kcal, cholesterol, and vitamin B2 intake.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, there are significant associations between lifestyles, sociodemographic characteristics, and clinical variables, and compliance with the recommended daily intakes. As shown by the results found in international studies, our work concludes that living in rural areas (because there are fewer accessible services), being divorced, and being illiterate negatively influence compliance with the recommended intakes of certain nutrients [6,19,30,31]. With regard to lifestyles, as in numerous research studies, we observed that a greater physical activity improves health and, in our case, there is greater compliance with the recommendations of Kcal, cholesterol, and vitamin B2 intake.…”
Section: Discussionsupporting
confidence: 78%
“…With regard to lifestyles, as in numerous research studies, we observed that a greater physical activity improves health and, in our case, there is greater compliance with the recommendations of Kcal, cholesterol, and vitamin B2 intake. This may be because people who are physically more active care more about their diet, and this has an impact on their health [19,32,33]. With regard to alcohol consumption, a higher compliance with recommended dietary intakes of Kcal, vitamin B2, potassium, and iodine is observed when alcohol is consumed regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have found significant associations between poor nutritional status and behavioral disturbances [31, 32, 33, 34, 35], worse cognitive status [31], and more impaired functioning in adult daily living activities [36, 37, 38, 39]. While these studies have demonstrated an association between nutritional status and aged population, very limited have examined the association of cognitive function with food addiction in young population and the majority of the studies have been conducted in clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Female older adults in our study reported lower DBP, handgrip strength and walking performance than males. In a study on Spanish older adults, Bibiloni et al (2018), reported that females had lower age-related physical fitness, educational level, as well as a greater weight than males.…”
Section: Discussionmentioning
confidence: 99%